EFEITO DA CALDA SULFOCÃLCICA SOBRE O ÃCARO Tetranychus mexicanus (MCGREGOR, 1950) EM CITROS - Andrade, Daniel JÃºnior de; Oliveira, Carlos Amadeu Leite de; Romani, Gustavo de NÃ³brega; Pattaro, Fernando Cesar (REVISTA DE AGRICULTURA, 2015)
EFEITO DA CALDA SULFOCÃLCICA SOBRE O ÃCARO Tetranychus mexicanus (MCGREGOR, 1950) EM CITROS